Feminisms - Kemp, Sandra; Squires, Judith (Oxford readers., 1998)
"Spanning nearly two decades, from 1980 to 1996, this Reader investigates the debates which have best characterized feminist theory. Including such articles as Pornography and Fantasy, The Body and Cinema, Nature as Female, and A Manifesto for Cyborgs, the extracts examine thoughts on sexualtiy as a domain of exploration, the visual representation of women, what being a feminist means, and why feminists are increasingly involved in political struggles to negotiate the context and meaning of technological development. With writings by bell hooks, Alice Jardine, and Andrea Dworkin, this multicultural Reader reflects the dynamic nature of feminist debates and the genuine diversity within current feminist theory. Capturing the sense of the rapid movement within feminist theory and criticism, Feminisms is ideal for anyone interested in feminism and the history behind it."--Publisher description